Role of Topical Phenytoin Dressing in Treatment of Split Thickness Skin Autograft Donor Site - Ubaid Ullah,; Rafiq, Mariam; Janjua, Azwa; Tahir, Atika; Aman, Nadir; Bashir, Kashif (Indus Journal of Bioscience Research, 2025)
Introduction: Burn injuries, mainly in pediatric patients, often use autografts for wound care. The donor site of a skin graft causes pain and takes time to heal. Phenytoin enhances wound healing by aiding fibroblast growth, reducing exudate, and promoting granulation tissue formation. This study compared the pain reduction and healing of donor site wound with phenytoin dressing and traditional Sufretulle gauze dressing. Methodology: A six-month randomized controlled trial occurred at Mayo Hospital, Lahore, involving 72 pediatric scald burn patients needing skin grafts. They were splited into Group 1 (Phenytoin dressing) and Group 2 (Sufretulle dressing), 36 patients each. Pain was monitored using FLACC and Wong-Baker FACES scales based on age. Wound healing progress was tracked using PUSH score on specific days. Data were analyzed with SPSS version 21, setting statistical significance at p ≤ 0.05. Results: The Phenytoin group had consistently lower pain scores than the Sufretulle group (p = 0.001). On Day 15, mean pain scores were 0.03 ± 0.16 for Phenytoin and 1.50 ± 0.97 for Sufretulle. Phenytoin group showed better wound healing (PUSH score: 2.56 ± 1.88) than Sufretulle group (6.67 ± 1.41, p = 0.001). No severe adverse effects were reported in either group. Conclusion: The use of topical phenytoin dressing showed faster wound healing and less pain at the donor site for skin grafts compared to sufretulle dressing. This cost-effective, low-risk option is a valuable alternative for managing donor sites in pediatric burn patients.